Hubungan Status Imunisasi Campak Dengan Kejadian Diare Pada Anak Usia 12-59 Bulan - Latifah Susilowati; Masta Hutasoit (Indonesian Journal of Nursing Research (IJNR), 2019)
Diarrhea is the second leading cause of infant mortality worldwide. InIndonesia, diarrhea is among the top 10 diseases handled in the Puskesmasand the top 10 inpatient diseases at regional hospitals. Measlesimmunization is recommended by the world health organization as aprevention and health care effort for children including prevention of theincidence of diarrhea. The general objective of this study was to determinethe relationship between measles immunization status and the incidenceof diarrhea in toddler in the work area of Kasihan Bantul Health Center.This study uses a case control research design with a retrospectiveapproach. Data collection began with data collection ages 12 - 59 monthssuffering from diarrhea in the last 6 months at the Kasihan Bantul HealthCenter. Then the researcher conducted homevisit to ask about the historyof measles immunization in children. The number of samples in thecontrol group was 44 children and the case group was 44 children. Theresults showed that there was no statistically significant relationshipbetween measles status and the incidence of diarrhea in children aged 12-59 months at the Kasihan Bantul Health Center. Health centers and healthworkers need to increase public awareness of the importance of measlesimmunization in infants as a form of support for government programs toprevent the occurrence of diarrhea.